The Use of Leaflet as A Health Education Media in Increasing The Knowledge of Complementary Feeding for Breastfeeding Mothers - Etty Nurkhayati; Nani Yunarsih; Febriana Sari; Mega Octamelia; Niken Bayu Argaheni (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
About a third of children around the world begin their untimely breastfeeding. Although several strategies have been implemented around the world to improve complementary feeding, progress has been slow. Improper feeding of complementary foods remains a significant global public health problem. The purpose of this study aims to determine the use of leaflets as a health education media in increasing the knowledge of complementary food in breastfeeding mothers. The study is Quasi-Experimental. with Pretest-Posttest with a Control Group. The Accidental Sampling sampling technique is breastfeeding mothers who have babies aged 7-24 months as many as 53 mothers as an experimental group and 53 mothers as a control group with the same criteria at the Posyandu of Belang Wetan Village. Primary data were collected with questionnaires containing objective questions. Secondary data with cohorts from village midwives. A hypothesis test is carried out after the pre-test, to find out whether or not there is an influence between free and bound variables, then using a paired sample t-test or paired sample t-test. The results of the analysis obtained a p-value of 0.000 less than 0.05. It can be concluded that there is an influence of health education methods using leaflet media and without using leaflet media on increasing knowledge that has a significant comparison of effectiveness. There is an influence of health education with leaflet media on increasing the knowledge of breastfeeding mothers about complementary feeding of breast milk in infants aged 7-24 months